Endoscopic Management of an Internal Laryngopyocele Presenting with Acute Airway Obstruction - Zenon Andreou; Premjit S. Randhawa; Paul O'Flynn; Francis M. Vaz (Case Reports in Surgery, 2011)
Statement of Problem. Laryngocele is a rare laryngeal disease, where there is an abnormal dilatation of the saccule of the laryngeal ventricle. It can either be internal or external, and a laryngopyocele is a rare complication of this anomaly. Internal laryngopyoceles can prove difficult to manage, as they often present with airway compromise. Method of Study. Case Report. Results. We present a case of a laryngopyocele that was successfully managed with suspension laryngoscopy and endoscopic marsupialisation and resection. To our knowledge, this is the first such case described in the literature. Conclusions. Surgical drainage of a laryngopyocele via the external approach is well documented in the literature. We feel that endoscopic resection of laryngopyoceles in an emergency situation is a viable alternative and also prevents the associated surgical morbidity.